Implementation of Flower Recognition using Convolutional Neural Networks - Hindarto, Djarot; Amalia, Nadia (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2023)
The recognition of flowers holds significant importance within the realms of ecological research, horticulture, and diverse technological applications. This study presents